Risk factors for voice disorders in public school teachers in Cyprus - Kyriakou, Kyriaki; Theodorou, Elena; Petinou, Kakia; Phinikettos, Ioannis (My University, 2020)
Aims: The purpose of this study was to investigate risk factors for self-perceived voice disorders in teachers in Cyprus in order to determine the necessity for a preventative vocal hygiene education program which could improve their work performance. Methods: An online questionnaire was completed by 449 teachers. The questionnaire extracted data regarding risk factors that may contribute to the development of voice disorders, occupational consequences of voice disorders and vocal hygiene education, as well as, a self-perceived severity of a participant's voice problem. Subjects were split into two groups, teachers with Voice Disorder Index (VDI)≤7 and teachers with VDI>7. The chi-squared test was used to explore the differences in responses for each voice risk factor, occupational consequence and vocal hygiene education between the two groups. Results: Teachers in the VDI> 7 group were more likely to frequently experience nasal allergies and respiratory infections, coughing, throat clearing, stress and yelling, have shorter breaks between classes, use loud voice, use their voice to discipline students, teach above students talking, etc. than teachers in the VDI≤7 group. Moreover, teachers in the VDI>7 group were more likely to limit their ability to perform certain tasks at work and reduce their activities or interactions "3-5 or more days"annually due to voice problems. Conclusions. Health, voice use, lifestyle, and environmental factors may play a part in the development of voice disorders in teachers and have an impact on their job. Therefore, a preventative vocal hygiene education program is suggested.
Keywords: Risk factors; Teachers, Cyprus; Voice disorders